Services and the National Information Infrastructure. Report of the Information Infrastructure Task Force Committee on Applications and Technology, Technology Policy Working Group. Draft for Public Comment - Office of Science and Technology Policy, Washington, DC.; Office of Science and Technology Policy, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
In this report, the National Information Infrastructure (NII) services issue is addressed, and activities to advance the development of NII services are recommended. The NII is envisioned to grow into a seamless web of communications networks, computers, databases, and consumer electronics that will put vast amounts of information at users' fingertips. Crucial to the development of an advance information infrastructure is the concept of NII "services," which manage the orderly flow of data and enable support applications. Many experts believe that the most critical aspect of the NII is the development of a services infrastructure; without it, access to the NII's advanced capabilities may be extraordinarily difficult and my not be affordable by the average citizen. An ongoing process of research, development, experimentation, and public debate, combined with commercial development and product deployment, is required to evolve a services framework and implementation.The Technology Policy Working Group recommends that: (1) high priority support continues to be needed in the 5 year strategic planning process the Committee on Information and Communications (CIC) is currently pursuing; (2) the coordinated government-wide R&D strategy for NII services which is under development by the CIC should continue to be closely coordinated and integrated with the progressive technology acquisition and deployment strategy being developed and implemented by the Information Infrastructure Task Force (IITF); and (3) government, industry, and academia should work closely together in pursuit of an advanced architectural framework for the NII services layer that supports interoperability while enabling individual commercially competitive solutions. Appendices include: "Representative High Performance Computing, Communications, and Information Technology's Information Infrastructure Technology and Applications (IITA) Tableau of Services" and "NII Forum--R&D for the NII: Technical Challenges, Services Research Recommendations." (MAS)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Information; Computer Networks; Cooperation; Government Role; Information Networks; Information Services; Information Technology; Program Development; Research and Development; Strategic Planning; Technological Advancement; Telecommunications; Users (Information); National Information Infrastructure; Reports, Evaluative